KEEFEKTIFAN MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTU MEDIA JANGTOR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV MI TARBIYATUL BANIN PERKALONGAN KABUPATEN PATI - Alaika, Asykar Luthfan (JGK (Jurnal Guru Kita), 2019)
Abstract: Effectiveness of Jangtor Media Think Pair Share Learning Model on the Ability to Solve Mathematical Problems in Grade IV Students of MI Tarbiyatul Banin Pekalongan Pati Regency. The purpose of this study was to determine the effectiveness of the think pair share learning model assisted by the media in improving students’ mathematical problem solving skills in FPB and KPK material. This type of research is to use the Pre Experimental Design that is used is the One Group Pretest-Posttest Design. The study population was all MI Tarbiyatul Banin Pekalongan students in the academic year 2017/2018. The sample taken was 32 fourth grade students. The data in this study were obtained through observation, interviews, tests, and documentation. The results of the study obtained the average pretest of 40.62 and the posttest average of 77.34. The results of the problem solving completeness test analysis of students showed reaching KKM (70). So it can be concluded that the media-assisted tps model is effective for improving mathematical problem-solving skills of fourth grade students at MI Tarbiyatul Banin Pekalongan Pati Regency. Keyword : Think Pair Share, Jangtor Media, Problem Solving Capabilities Abstrak : Keefektifan Model Pembelajaran Think Pair Share Berbantu Media Jangtor Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas IV MI Tarbiyatul Banin Pekalongan Kabupaten Pati. Tujuan dalam penelitian ini adalah untuk mengetahui efektifitas model pembelajaran think pair share berbantu media jangtor dalam meningkatkan kemampuan pemecahan masalah matematika siswa pada materi FPB dan KPK. Jenis penelitian ini adalah menggunakan Pre Experimental Desaign yang digunakan adalah One Group Pretest- Posttest Desaign. Populasi penelitian adalah seluruh siswa MI Tarbiyatul Banin Pekalongan tahun pelajaran 2017/2018. Sampel yang diambil adalah 32 siswa kelas IV. Data dalam penelitian ini diperoleh melalui observasi, wawancara, tes, dan dokumentasi. Hasil penelitian diperoleh rata-rata pretest 40,62 dan rata-rata posttest 77,34. Hasil analisis tes ketuntasan pemecahan masalah siswa menunjukkan mencapai KKM (70). Jadi dapat disimpulkan bahwa model tps berbantu media jangtor efektif untuk meningkatkan kemampuan pemecahan masalah matematika siswa kelas IV MI Tarbiyatul Banin Pekalongan Kabupaten Pati. Kata Kunci : Think Pair Share, Media Jangtor, Kemampuan Pemecahan Masalah